E0115 Overexpression and inhibition of Camk2d gene in primary myocardial cells by lentivirus. (17th November 2010) - Yao, Qin; Song, Zhiyuan; Tong, Shifei; Wan, Ying; Cheng, Jun; Ding, Xiang
Abstract : Purpose: It has been found that Camk2d (calcium/calmodulin dependent protein kinase II delta) is related to E-C couple and myocardial hypertrophy and heart failure in pathological states. Moreover, its function alteration may play some role in arrhythmia. To further investigate the mechanism of Camk2d in onset and development of arrhythmia, we have built a platform for next stage by overexpressing Camk2d in myocardial cells by lentivirus transduction and inhibiting it by RNAi. Method (1) Rat Camk2d ORF was cloned by PCR, ligated into lentivirus vector and then packaged into lentivirus particles. (2) 3 shRNA sequences against Camk2d were designed and cloned. The one with highest inference efficiency was then screened by westernblot following with calcium phosphate transfection on 293 cells. (3) The selected RNAi clone was packaged into lentivirus particles. (4) Cultured myocardial cells from neonatal rats were transducted with overexpression or RNAi lentivirus and harvested for analysing Camk2d level by Realtime-PCR and westernblot. Result: Myocardial cells transducted by overexpression lentivirus exhibited an over 5-time higher level of Camk2d than normal, while in RNAi transfected cells, expression of Camk2d decreased by around 50%. Conclusion: Lentivirus can efficiently transduct primary myocardial cells with exogenous genes to obtain cells with special gene up- or down-regulated.